(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study re-examines experimental data from a Taguchi L9 orthogonal array (cutting speed: 34–134 m/min, feed: 0.1–0.3 mm/rev, depth of cut: 1–3 mm) to identify a threshold-based "catastrophic wear zone" for HSS tool operation in dry turning of aluminum. While conventional Taguchi optimization ranks cutting speed as the most influential factor affecting tool life (delta S/N = 16.14 vs. 6.87 for feed and 1.10 for depth), a closer inspection reveals a non-linear deterioration pattern. All three experiments conducted at 134 m/min produced the lowest tool life responses (45, 26, and 17 minutes), representing a 73.6% reduction compared to the optimal parameter combination. The S/N ratio collapses from 44.80 (at 90 m/min) to 28.66 (at 134 m/min)—a 36% deterioration in signal-to-noise performance. This threshold behavior establishes 134 m/min as a critical speed boundary beyond which tool life becomes both significantly shorter and highly inconsistent. Based on these findings, a recommended safe operating window is proposed: cutting speed ≤ 90 m/min, feed ≤ 0.2 mm/rev, and depth of cut ≤ 2 mm, with a red-flag warning against simultaneous use of 134 m/min and 0.3 mm/rev. The practical implications for TVET workshops, where unplanned tool failure disrupts training schedules and increases material costs, are discussed.